Study of the effects of type I and type II diabetes using the logistic regression model - Onu, Obineke Henry; Ejukwa, Justin Odadami; Anyamele, Godspower A (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2024)
The study of the effects of type I and type II diabetes using Logistic regression was considered. The data used was in the year 2021, obtained from the University of Port Harcourt Teaching Hospital (UPTH), Port Harcourt. The study employed, chi-square, p-value, goodness of fit test, and analysis of variance. It was observed that type II diabetes was more dangerous than type I. Also, the type 2 diabetes has a more negative effect on the patients than the type I. It was also found that both type I and type II are unsafe for one’s health.